Effect of Canagliflozin on Heart Function Involving Ketone Bodies in Patients with Type 2 Diabetes - Kutoh, Eiji; Hayashi, Jyunka (Drug Research, 2019)
This report describes the effect of administration (n=3) or withdrawal (n=2) of canagliflozin, a sodium-glucose co-transporters 2 (SGLT-2) inhibitor, on cardiac function in relation to ketone bodies. Three cases received and two cases discontinued canagliflozin. Changes of heart function with ultrasonography (EF: ejection fraction and %FS: functional shortening) and cardiometabolic parameters including ketone bodies (acetoacetate/beta-hydroxybutylate) were compared at 3 months. 69, 68 and 60 years old male patients A, B and C, respectively with moderately decreased heart function received canagliflozin 100 mg/day. EF, %FS and acetoacetate/beta-hydroxybutylate levels increased. 60 and 59 years old female patients D and E with normal and borderline heart function, respectively discontinued canagliflozin 50 mg/day. EF, %FS and acetoacetate/beta-hydroxybutylate levels decreased. Taken together, these results suggest that concomitant changes between ketone bodies and heart function were observed with or without canagliflzoin. This drug might have effects on cardiac function through modulating ketone bodies.
Keywords: SGLT-2 inhibitors; canagliflozin; ketone body; heart function